Typifications, a new synonym and new distribution data in Ficaria (Ranunculaceae) - Paszko, Beata; Paul, Wojciech; Nikel, Agnieszka; Musiał, Lucyna (Phytotaxa, 2020)
Lectotypes for five infraspecific names of Ranunculus ficaria (currently known as Ficaria verna s.str.) (Ranunculaceae) described by Hugo Zapałowicz are proposed. Four of these names are established synonyms of Ficaria verna s.str. Ranunculus ficaria var. bessarabicus is considered to be a new synonym of F. grandiflora, which is newly recorded for Moldova. Revised syntypes represent three species of Ficaria: F. verna s.str., F. grandiflora, and F. calthifolia. The exact dates of publication for parts 12 and 13 of Zapałowicz’s work entitled Conspectus florae Galiciae criticus published in the journal Rozprawy Wydziału Matematyczno-Przyrodniczego Akademii Umiejętności, Seria III, Dział B. Nauki Biologiczne are corrected based on the publisher’s catalogue.